2003
DOI: 10.1002/lsm.10202
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of oral lichen planus with the 308‐nm UVB excimer laser—early preliminary results in eight patients

Abstract: The preliminary results in our opinion warrant further studies of this treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
2
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 13 publications
0
36
2
2
Order By: Relevance
“…Soliman et al 15 observed recurrence of OLP in only 3 patients out of 25 over period of 6-month follow up following the use of diode laser. The results in our study were contrast with studies conducted by Passeron et al, 18 Trehan and Taylor, 19 Kollner et al 20 Passeron et al 18 conducted a study using 308 nm-excimer lasers to treat erosive OLP in four patients with previous treatment failures, where 12 sessions were attended during 6 weeks, one patient showed partial remission, 2 were resistant to treatment and the other patient showed exacerbation of the lesion. The present study was conducted on patients, without any previous treatment of the lesion, while in the abovementioned studies, refractory cases were considered with different wavelengths (308 nm) compared to the present study (980 nm).…”
Section: Discussioncontrasting
confidence: 99%
“…Soliman et al 15 observed recurrence of OLP in only 3 patients out of 25 over period of 6-month follow up following the use of diode laser. The results in our study were contrast with studies conducted by Passeron et al, 18 Trehan and Taylor, 19 Kollner et al 20 Passeron et al 18 conducted a study using 308 nm-excimer lasers to treat erosive OLP in four patients with previous treatment failures, where 12 sessions were attended during 6 weeks, one patient showed partial remission, 2 were resistant to treatment and the other patient showed exacerbation of the lesion. The present study was conducted on patients, without any previous treatment of the lesion, while in the abovementioned studies, refractory cases were considered with different wavelengths (308 nm) compared to the present study (980 nm).…”
Section: Discussioncontrasting
confidence: 99%
“…Topical application of psoralen is promising, but still experimental [17]. There was several case series which showed that treatment with the 308-nm excimer laser might be an additional treatment option for OLP [18][19][20]. However the results are still disappointing, so searching for new treatment modalities seems quite rational.…”
Section: Discussionmentioning
confidence: 99%
“…Aghahosseini et al [103] experienced the treatment of 26 lesions in 13 patients, evaluating the signs, symptoms and size of the lesions. A diode laser (632 nm, 120 J/cm 2 ) for 2 minutes was used.…”
Section: Laser Therapymentioning
confidence: 99%